Formation of NaH Molecules in the Lowest Rovibrational Level of the Ground Electronic State via Short-Range Photoassociation. (28th November 2014) - Li, Jinglun; Huang, Yin; Xie, Ting; Chai, Shuo; Cong, Shulin
Abstract: The formation of NaH molecules in the lowest rovibrational level of the ground electronic state is investigated using a pump-dump photoassociation (PA) scheme. In short-range region, two colliding atoms Na and H are efficiently associated into the NaH molecule in the rovibrational |0, 0〉 state of the ground electronic state via the intermediately rovibrational |10, 1〉 state of the excited electronic state. The changes of populations with the electric field amplitudes, frequency detunings, dump pulse duration and delay time between two laser pulses are calculated and discussed. The PA probability reaches 0.623 with a high state-selectivity.